The Correlation of the Perception of Early Detection Cervical Cancer with Attitude to do Visual Inspection with Acetic Acid - Laily Prima Monica; Maria Ulfa (Journal of Ners and Midwifery, 2020)
Cervical cancer is a malignant tumor that grows in the uterus / cervix which is the lowest part of the uterine core and is attached to the top of the vagina. The high incidence of cervical cancer in Indonesia is due to a lack of knowledge and perception of women to prevent the development of cervical cancer. The incomprehensive information about IVA test exposure is as the cause of the women didn't want to do the test. Lack of knowledge about the process of IVA test, feel fear and shame including feeling against to religion principles as the inhibitor factors to do test. Method :The research design uses correlational design with a cross-sectional approach. The study population is 30 respondents and the sample consisted of 27 respondents using purposive sampling technique. Data were analyzed using Spearman rank. Results: The research data showed that there was a relationship between the level of perception of mothers about cervical cancer and the attitude of mothers to carry out the IVA test (Visual Inspection with Acetic Acid) p value = 0,000, so the p value = 0,000 <0.05 while r = 0.678. The relationship of perception with attitude shows that more than half of the respondents 66% have a positive perception in early detection of cervical cancer and they are positive about IVA (Visual Inspection with Acetic Acid).